Keter Malkhut (Coroa Real) e a mística filosófica de Ibn Gabirol (Keter Malkhut (Kingly Crown) and the philosophical mysticism of Ibn Gabirol) - DOI: 10.5752/P.2175-5841.2012v10n27p728 - Cavaleiro de Macedo, Cecilia Cintra (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2012)
Ibn Gabirol foi um poeta e filósofo judeu espanhol que viveu no século XI. Sua filosofia racional, redigida em árabe, parece ser completamente desvinculada de sua poesia religiosa hebraica, considerada mística. Alguns estudiosos entendem que entre mística e filosofia existe um antagonismo insuperável. Redigido no período de formulação da Kabbalah, o poema Keter Malkhut, pela estreita relação que seu conteúdo mantém com alguns elementos filosóficos usados pelo autor, foi freqüentemente interpretado como mera alegoria estética para o sistema metafísico desenvolvido em sua obra filosófica Fons Vitae. Este artigo visa oferecer uma reflexão introdutória sobre a mística judaica e, à luz desta, analisar a primeira parte do poema frente ao modelo metafísico apresentado no Fons Vitae. A partir de uma discussão sobre linguagem e simbolismo, surge a idéia de que tanto a poesia religiosa quanto a filosofia racional de Ibn Gabirol sejam frutos de uma única intuição inicial, inspirada na especulação mística milenar sobre o Trono da Glória (Merkabah), mas nos quais já podemos entrever certos elementos neoplatônicos que caracterizarão o novo modelo da Kabbalah. Palavras-chave: Kabbalah.Trono da Glória. Ibn Gabirol. Neoplatonismo. Mística Judaica. Abstract Ibn Gabirol was a Jewish Spanish poet and philosopher that lived in the 11th century. His rational philosophy written in Arabic seems to be completely disconnected with his Hebrew religious poetry, considered as mystical. Some scholars believe that there is an insuperable antagonism between mysticism and philosophy. Composed during the formative period of the Kabbalah, the poem Keter Malkhut was repeatedly seen as a mere aesthetic allegory of the metaphysical system developed in his philosophical work Fons Vitae, due to the close relation that its contents hold with some philosophical elements. This paper aims to offer an introductory reflection about Jewish mysticism and, in the light of this, to analyze the first part of the Keter Malkhut in face of the metaphysical structure presented in Fons Vitae. From a discussion about language and symbolism, emerges the idea that both Ibn Gabirol’s religious poetry and his rational philosophy are different products of a single initial intuition, inspired by the millenary Jewish mystical speculation concerning the Throne of Glory (Merkabah), but in which we could see certain Neo-platonic elements that will distinguish the new movement of Kabbalah. Keywords: Kabbalah. Throne of Glory. Ibn Gabirol. Neo-Platonism. Jewish Mysticism.